REAPING BENEFITS THROUGH EFFECTIVE PEER REVIEW IN A COLLABORATIVE LANGUAGE CLASSROOM - Vaida Misevičiūtė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2022)
Research studies now and again promote alternative assessment tools because they engage students in reflective practices that do not only improve the quality of the acquired knowledge, but also enhance responsibility towards working and learning ultimately developing lifelong learning skills. Literature review revealed that many practitioners doubt the value of reflective practice through a process of peer learning and peer assessment claiming the activities are too time consuming and students are not mature enough or lack confidence and motivation to assess peers critically. The aim of the research is to assess students’ perception of peer and teacher evaluations. The research is based on a process peer assessment and evaluation activity that has been carried out with the university students in C1 General English class over the two very different semesters: one regular and one online (affected by COVID-19). The course under investigation has been designed based on the best practices that have been discovered through literature review like modeling, oral feedback, peer review forms, classroom atmosphere, and cultural aspects of review. Against general perception, students seemed to enjoy the peer review process and valued it even more than teacher feedback when the peer reviewers were motivated. Engagement in peer review online demonstrated even deeper subject learning along with demonstration of lifelong learning skills. Several comments alluded to the idea that the learning process was more rewarding than final evaluation. Reflective practice in this process assignment showed enhanced students’ engagement in learning, reflection, and peer evaluation; therefore, supporting clear benefits for students and teachers engaged in the activity, and overall value that the reflective assignment has on learning.